Epidemiological characteristics of respiratory viruses in hospitalized children during the COVID-19 pandemic in southwestern China - Zhu, Lin; Luo, Tingting; Yuan, Yining; Yang, Shu; Niu, Chao; Gong, Ting; Wang, Xueer; Xie, Xiaohong; Luo, Jian; Liu, Enmei; Fu, Zhou; Tian, Daiyin (Frontiers in Cellular and Infection Microbiology, 2023)
Background Multinational studies have reported that the implementation of nonpharmaceutical interventions (NPIs) to control severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission coincided with the decline of other respiratory viruses, such as influenza viruses and respiratory syncytial virus. Objective To investigate the prevalence of common respiratory viruses during the coronavirus disease 2019 (COVID-19) pandemic. Methods Respiratory specimens of children with lower respiratory tract infections (LRTIs) hospitalized at the Children’s Hospital of Chongqing Medical University from January 1, 2018 to December 31, 2021 were collected. Seven common pathogens, including respiratory syncytial virus (RSV), adenovirus (ADV), influenza virus A and B (Flu A, Flu B), and parainfluenza virus types 1–3 (PIV1–3), were detected by a multiplex direct immunofluorescence assay (DFA). Demographic data and laboratory test results were analyzed. Results 1) A total of 31,113 children with LRTIs were enrolled, including 8141 in 2018, 8681 in 2019, 6252 in 2020, and 8059 in 2021.The overall detection rates decreased in 2020 and 2021 (P < 0.001). The detection rates of RSV, ADV, Flu A, PIV-1, and PIV-3 decreased when NPIs were active from February to August 2020, with Flu A decreasing most predominantly, from 2.7% to 0.3% (P < 0.05). The detection rates of RSV and PIV-1 resurged and even surpassed the historical level of 2018–2019, while Flu A continued decreasing when NPIs were lifted (P < 0.05). 2) Seasonal patterns of Flu A completely disappeared in 2020 and 2021. The Flu B epidemic was observed until October 2021 after a long period of low detection in 2020. RSV decreased sharply after January 2020 and stayed in a nearly dormant state during the next seven months. Nevertheless, the detection rates of RSV were abnormally higher than 10% in the summer of 2021. PIV-3 decreased significantly after the COVID-19 pandemic; however, it atypically surged from August to November 2020. Conclusion The NPIs implemented during the COVID-19 pandemic affected the prevalence and seasonal patterns of certain viruses such as RSV, PIV-3, and influenza viruses. We recommend continuous surveillance of the epidemiological and evolutionary dynamics of multiple respiratory pathogens, especially when NPIs are no longer necessary.